India's economic growth history: fluctuations, trends, break points and phases - Virmani, Arvind (2006)
This paper reviews India's growth performance since independence. One of the innovations in this paper is to take explicit account of rainfall variations that play a very important role in the Indian economy. This allows us to determine whether the Indian economy has become less dependent on the monsoons (`drought proof'). It also allows a statistically more accurate determination of the different phases of Indian economic growth. These phases are linked to different policy regimes and therefore allow us to evaluate the impact of a set of policies on economic growth. - Reproduced.
Keywords: Economic growth - India; Economic growth